E-Tax System Adoption and Tax Compliance: The Role of Taxpayers Satisfaction, Taxpayers’ System Competence in the Post Covid-19 Pandemic Era - Bojuwon, Mustapha; Ogunleye, Funmilola Mary; Aduwo, Olola Olayeye; Ogunleye, Akinyemi Wumi; Adeogun, Adekunle Sunday; Olasehinde, Sunday Adeniyi; Adebayo, Adesodun Isaac; Ekundayo, Ayodele Temitope; Aduwo, Ayomikun Elizabeth; Ogunrinde, Olufemi Philip (International Review of Management and Marketing, 2026)
This study examined the nexus between e-tax system adoption and tax compliance through the mediating and moderating role of taxpayer satisfaction and taxpayer system competence in the post Covid-19 pandemic era in Nigeria. A quantitative method of analysis was employed through an adapted questionnaire which was distributed to 480 taxpayers, asking about their thoughts on e-tax system adoption regarding compliance costs, security, quality of service, and time spent filing returns.[1] The findings reveal a significant and positive relationship between each element of hypothesis one (H1a-d) and tax compliance. Hypotheses 2b, 2c, and 2d also showed significant positive relationships with taxpayer satisfaction. However, cost as an e-tax system adoption factor did not significantly affect taxpayer satisfaction (H2a: β = -0.051, t = 0.153, p = > 0.010). Conversely, H3 revealed a substantial and positive correlation between e-tax system competency and tax compliance (β = 0.042, t = 5.606, p = < 0.05). The indirect effect of taxpayer satisfaction on the link between e-tax system adoption influencers and tax compliance was also found to be significant, while social media did not significantly moderate the SAT-SMP path to a positive level (H4a-d: β = 0.078, t = 0.564, p > 0.05). By providing useful information on taxpayer satisfaction and e-tax system competence, the study offers new insights into the factors influencing e-tax adoption and compliance in a developing country. This information can be used to inform policy and practice in Nigeria.